PENGARUH KONSEP SISTEM DAN LINGKUNGAN DALAM MODIFIKASI CUACA TERHADAP PENINGKATAN CURAH HUJAN DAN KETERSEDIAAN AIR DI DAS CITARUM - Sutopo Purwo Nugroho (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2001)
Weather modification technology was applied in Citarum Watershed – West Java on 12 March – 10 April 2001 for increase water resources in Saguling, Cirata and Jatiluhur Dams. The application was based indication of Citarum River inflow decreased at the end of 2001 that so three cascade dams had water storage deficits. Weather modification technology by employing system and environment concept has been increase the rainfall and inflow of Citarum Watershed. The average inflow of Citarum River was 326,81 m3/sec and nett volume storage in the dams were 559,06 million m3.